[Translated article] Selection of Quality Indicators for the Certification of Dermato-Oncology Units: The CUDERMA Project Delphi Consensus Study - I. Martínez de Espronceda Ezquerro; S. Podlipnik; J. Cañueto; A. de la Cuadra-Grande; C. Serra-Guillén; D. Moreno; L. Ferrándiz; J. Domínguez-Cruz; P. de la Cueva; Y. Gilaberte; S. Arias-Santiago (Elsevier, 2023)
Quality indicators are crucial for standardizing and guaranteeing the quality of health care practices. The Spanish Academy of Dermatology and Venereology (AEDV) launched the CUDERMA Project to define quality indicators for the certification of specialized units in dermatology; the first 2 areas selected were psoriasis and dermato-oncology. The aim of this study was to achieve consensus on what should be evaluated by these indicators using a structured process comprising a literature review and selection of an initial list of indicators to be evaluated in a Delphi consensus study following review by a multidisciplinary group of experts. The selected indicators were evaluated by a panel of 28 dermatologists and classified as either "essential" or "of excellence". The panel agreed on 84 indicators, which will be standardized and used to develop the certification standard for dermato-oncology units. Resumen: Los indicadores de calidad son una herramienta clave como garantía de calidad y homogenización de la asistencia sanitaria. En este contexto, la Academia Española de Dermatología y Venereología ha diseñado el proyecto Certificación de unidades de dermatología (CUDERMA), una iniciativa que busca definir indicadores de calidad para certificar unidades de dermatología en distintos ámbitos, entre los que se seleccionaron psoriasis y dermato-oncología de forma inicial. Este estudio tuvo por objetivo consensuar los aspectos a evaluar por los indicadores, siguiendo un proceso estructurado para la revisión bibliográfica y elaboración de un set preliminar de indicadores, revisado por un grupo multidisciplinar de expertos, para su evaluación mediante un Consenso Delphi. Un panel de 28 dermatólogos evaluó los indicadores y los clasificó como «básicos» o «de excelencia», generando un conjunto de 84 indicadores consensuados que serán estandarizados para diseñar la norma para certificar las unidades de dermato-oncología.